Topological phase transition driven by magnetic field and topological Hall effect in an antiferromagnetic skyrmion lattice - Tomé, Martín (2021)
The topological Hall effect (THE), given by a composite of electric and topologically nontrivial spin texture is commonly observed in magnetic skyrmion crystals. Here we present a study of the THE of electrons coupled to antiferromagnetic skyrmion lattices (AF-SkX). We show that, in the strong Hund coupling limit, topologically nontrivial phases emerge at specific fillings. Interestingly, at low filling an external field controlling the magnetic texture drives the system from a conventional insulator phase to a phase exhibiting the THE. Such behavior suggests the occurrence of a topological transition which is confirmed by a closing of the bulk gap that is followed by its reopening, appearing simultaneously with a single pair of helical edge states. This transition is further verified by the calculation of the Chern numbers and Berry curvature. We also compute a variety of observables in order to quantify the THE, namely, Hall conductivity and the orbital magnetization of electrons moving in the AF-SkX texture.